Stapled diaphragm resection: A new approach to diaphragmatic cytoreductive surgery for advanced-stage ovarian cancer. (December 2022) - Huber, Daniela; Fournier, Ian; Christodoulou, Michel; Seidler, Stéphanie; Besse, Valérie; Mathey, Marie-Pierre; Nef, James; Hurni, Yannick
Abstract: Objective: To evaluate a novel technique for diaphragmatic full-thickness resection (DFTR) using a vascular stapler to perform cytoreductive surgeries in patients with advanced ovarian cancer. Study Design: Single-center retrospective analysis of consecutive patients with advanced-stage ovarian cancer undergoing stapled diaphragmatic full-thickness resections (S-DFTRs) as part of cytoreductive surgeries between January 2018 and June 2022, according to the IDEAL recommendations. Results: Fifteen patients underwent cytoreductive surgeries with S-DFTRs. The median operative time was 300 (114–547) minutes. Cytoreduction was considered complete in all cases. All S-DFTRs were performed on the right diaphragm. Concomitant left diaphragmatic peritoneal stripping was performed in 5 cases (33.3%) and was associated with a conventional DFTR in 1 case (6.7%). Prophylactic intraoperative tube thoracostomy was never required. Four patients (26.7%) were admitted to the intensive care unit. Pleural effusion was observed in 9 patients (60.0%), and 4 (26.7%) required a postoperative pigtail catheter thoracostomy. Three patients (20.0%) required catheter placement on the right hemithorax (ipsilaterally to the S-DFTR) and 2 patients (13.3%) required catheters on the left hemithorax (contralaterally to the S-DFTR). Pneumothorax requiring tube thoracostomy was observed in 1 case (6.7%) on the left hemithorax (contralaterally to the S-DFTR). Pulmonary embolism and pneumonia were both observed once (6.7%). The median hospitalization length was 14 (5–36) days. During the follow-up, 6 patients (40.0%) had a recurrence, but none involved the pleura or the diaphragm. According to the IDEAL classification, this study could be ranked as stage 2a (development). Conclusions: This technique appears to be a fast and safe method for performing diaphragmatic cytoreductive surgeries and could reduce postoperative complications.